From friends to foes: fungi could be emerging marine sponge pathogens under global change scenarios - Pérez-Llano, Yordanis; Yarzábal Rodríguez, Luis Andrés; Martínez-Romero, Esperanza; Dobson, Alan D. W.; Gunde-Cimerman, Nina; Vasconcelos, Vitor; Batista-García, Ramón Alberto (Frontiers in Microbiology, 2023)
Global change, experienced in the form of ocean warming and pollution by man-made goods and xenobiotics, is rapidly affecting reef ecosystems and could have devastating consequences for marine ecology. Due to their critical role in regulating marine food webs and trophic connections, sponges are an essential model for studying and forecasting the impact of global change on reef ecosystems. Microbes are regarded as major contributors to the health and survival of sponges in marine environments. While most culture-independent studies on sponge microbiome composition to date have focused on prokaryotic diversity, the importance of fungi in holobiont behavior has been largely overlooked. Studies focusing on the biology of sponge fungi are uncommon. Thus, our current understanding is quite limited regarding the interactions and “crosstalk” between sponges and their associated fungi. Anthropogenic activities and climate change may reveal sponge-associated fungi as novel emerging pathogens. Global change scenarios could trigger the expression of fungal virulence genes and unearth new opportunistic pathogens, posing a risk to the health of sponges and severely damaging reef ecosystems. Although ambitious, this hypothesis has not yet been proven. Here we also postulate as a pioneering hypothesis that manipulating sponge-associated fungal comunities may be a new strategy to cope with the threats posed to sponge health by pathogens and pollutants. Additionally, we anticipate that sponge-derived fungi might be used as novel sponge health promoters and beneficial members of the resident sponge microbiome in order to increase the sponge's resistance to opportunistic fungal infections under a scenario of global change.